The Role of Nonseparable Utility and Nontradeables in International Business Cycles and Portfolio Choice - Matsumoto, Akito (IMF Working Papers; Working Paper ;, 2007)
This paper analyzes the role of nonseparable utility and nontradables in business cycles and portfolio choice. I find that nonseparability in utility can change the portfolio choice significantly. Unlike previous results in literature, the optimal portfolio of the traded-good sector equities is no longer a well diversified portfolio and becomes sensitive to parameter values. As a result, the model often generates extreme home bias or anti-home bias portfolios implying that some frictions in asset markets, which prevent agents from holding these extreme portfolios, can explain the lack of international risk sharing.